Analysis and Simulation of Transient Contact Stress and Temperature Field of Polymer Gear - Wang Zhen; Wang Yanjun; Wang Jingjing; Mao K (Jixie chuandong)
The contact pressure of the tooth surface of the polymer gear is analyzed by using the method of Hertz contact theory and finite element contact analysis. The calculation method of the tooth surface friction coefficient and the friction heat flux density of the gear tooth during the meshing process is studied. The simulation method of temperature field and stress in the instantaneous contact temperature of the gear teeth during the meshing transmission of PEEK polymer gear is discussed. The direct coupling method is used to analyze the heat-structure of the gears,and the transient temperature field and stress are obtained. The results of the initial ambient temperature are discussed. The results show that the increase of the initial ambient temperature has a great influence on the temperature field and the stress at the time of meshing.